Analysis of multicrystal pump–probe data sets. I. Expressions for the RATIO model. Issue 5 (1st September 2014) - Fournier, Bertrand; Coppens, Philip
<x xml:space="preserve">Abstract</x> The RATIO method in time‐resolved crystallography [Coppens et al. (2009). J. Synchrotron Rad.16, 226–230] was developed for use with Laue pump–probe diffraction data to avoid complex corrections due to wavelength dependence of the intensities. The application of the RATIO method in processing/analysis prior to structure refinement requires an appropriate ratio model for modeling the light response. The assessment of the accuracy of pump–probe time‐resolved structure refinements based on the observed ratios was discussed in a previous paper. In the current paper, a detailed ratio model is discussed, taking into account both geometric and thermal light‐induced changes.